ANALISIS KINERJA RANTAI PASOKAN MENGGUNAKAN METODE SUPPLY CHAIN OPERATION REFERENCE - Tommy Saptiadi; Nining Koesdiningsih (Jurnal Fokus Manajemen Bisnis, 2022)
In recent years, supply chain performance meassurement has received a lot of attention from researchers and practitioners. Effective supply chain management is one of the potential ways to improve supply chain performance and competitive advantage. This study aims to determine the supply chain performance at PT. Bimandiri Agro Sedaya by using the  Supply Chain Operation Reference (SCOR) method analyzes the problems that occur in the company, then provides solutions to the problems to improve company performance. This study used a descriptive quantitative research method with the case study technique. Data collection techniques used structured and unstructured interviews with the human resource development members and observations to determine the supply chain condition. The secondary data obtained from the company were company reports and documentation. The results of this performance measurement obtained from the performance attributes in the SCOR are as follow: (1) Perfect Order Fulfillment (POF) with an actual result of 65,91% and a reference value of 80%, (2) Order Fulfillment Cycle Time (OFCT) with the duration of the supply chain process is by the company's target of 1 day, (2) Cost of Good Sold (COGS) of 65,09% still not appropriate with expectations with a reference target of 48% and (4) Cash to Cash Cycle Time (CTCCT) of 14 days still has not reached the company's target of 7 days.